2021
DOI: 10.1088/1674-1137/abcf20
|View full text |Cite
|
Sign up to set email alerts
|

Minimal length effects on motion of a particle in Rindler space *

Abstract: Various quantum theories of gravity predict the existence of a minimal measurable length. In this paper, we study effects of the minimal length on the motion of a particle in the Rindler space under a harmonic potential. This toy model captures key features of particle dynamics near a black hole horizon and allows us to make three observations. First, we find that chaotic behavior becomes stronger with increases in minimal length effects, leading predominantly to growth in the maximum Lyapunov characteristic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…As elaborated in Ref. [31], this result does not necessarily show that the bound conjectured in Ref. [6] is violated.…”
Section: Conclusion and Discussionmentioning
confidence: 56%
“…As elaborated in Ref. [31], this result does not necessarily show that the bound conjectured in Ref. [6] is violated.…”
Section: Conclusion and Discussionmentioning
confidence: 56%
“…In [39], Ge et al believed that this violation was related to the stability of the black holes, and it is possible to solve this violation phenomenon through research on stability. In [42,43], the authors found the violation by exploring the influence of the minimum length effects on the chaotic motion. They believed that this result is not a violation for the conjecture proposed in [31], and the bound can be corrected by the minimum length in the bulk.…”
Section: Discussionmentioning
confidence: 99%
“…There are two explanations for the violation of the bound. In [51,52], the authors discussed the minimal length effects on the chaotic motion of the particle, and found that the bound is violated. They believed that the result does not necessarily implies the violation for the bound conjectured in [11], and the bound should be corrected due to the minimal length in bulk.…”
Section: Conclusion and Discussionmentioning
confidence: 99%